Ultraviolet sensing based on nanostructured ZnO/Si surface acoustic wave devices. (3rd November 2015) - Guo, Y J; Zhao, C; Zhou, X S; Li, Y; Zu, X T; Gibson, D; Fu, Y Q
Abstract: An ultraviolet (UV) sensor based on nanostructured zinc oxide (ZnO)/Si surface acoustic wave (SAW) devices was studied in this paper. The ZnO films sputtered onto Si (100) substrate showed a preferred (0002) orientation and good photoluminescence emission. For an SAW device with a wavelength of 64 μ m, a frequency downshift of ∼1.4 kHz was observed for the Rayleigh mode under a UV light intensity of 0.6 mW cm −2, whereas the frequency downshift for the Rayleigh mode was increased to 8.3 kHz after integrating ZnO nanorods (NRs) in the ZnO/Si SAW devices. For the SAW device with a wavelength of 20 μ m irradiated under a UV light intensity of 0.6 mW cm −2, a frequency downshift of 25 kHz for the Sezawa mode was obtained compared to a shift of 12 kHz for the Rayleigh mode. After depositing ZnO NRs, the resonant frequency for the Rayleigh mode was increased to 27.4 kHz under the same UV intensity illumination, due to the significant increase in surface-to-volume ratio.